PENGARUH KONDISI FISIK TERHADAP KETERAMPILAN BERMAIN TENIS LAPANGAN - Imel M Sihombing; Eprain Sormin; Maulana Alkahfi Pohan; Arkan Fahlevi; Nurkadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to examine the impact of physical condition on tennis playing ability. Physical condition is an essential element in the performance of tennis athletes, as this sport requires quick reaction speed, muscle strength, agility, stamina, and good hand-eye coordination. The method used in this study is a quantitative approach with a correlational design. The participants consisted of 30 junior tennis athletes from Medan City. The data collection instruments included physical condition tests (speed, agility, strength, stamina, and coordination) as well as tennis skill tests (serve, forehand, backhand, and volley). The findings indicate a significant relationship between physical condition and tennis playing ability (r = 0.78; p < 0.05). In actual play, athletes with better physical fitness levels demonstrated more consistent technical skills and more stable performance during matches. Therefore, improved physical condition has been shown to have a positive effect on technical mastery and the effectiveness of tennis performance.